Visual archives and infographics: new connections - Fernandes, Marta (2022)
The present article is part of a broader study that frames the concept and creation of visual archives for online press, in relation to in-‐ fographics. In addition to being an operative discipline, Design presents it-‐ self as a theoretical response, through the analysis of conditionings in soci-‐ ety and the anticipation of new communication processes. By presenting and promoting the practical and theoretical investigation in areas such as design and visual literacy, with specificity on infographics – a multidisciplinary area in constant evolution –, we intend to reveal how we can communicate complex information content visually. Focusing on online press infographics, we propose to establish a new role by relating it to visual archives. Nowadays, the Internet offers various resources for online archives and databases. In the interest of preserving content and data, various archives are, currently, committed to digitizing their information. Various govern-‐ ments, in a methodical manner, have made budget and government deci-‐ sions available online. Other examples, like Google, are also a vital source of information. However, correlations are dispersed and its logic is pre-‐ sented based on textual parities or presented in datasets that only make sense to a scarce number of people. Archives, as a specific field in information, should propose systemic con-‐ structions between content and meaning. This is the underlying premise, when we question in what measure can archives, by becoming visual, solve flaws in communication. At the same time, the subjacent objective of most information visualization is to organize and clarify mass volumes of data. Based on this definition, it is a field that has impinged it self in the concept of archive. We will begin explaining the connections that make information visualization fertile ground for this concept, by decoding the definition and objectives of archives. After, through authors and case studies, we will ana-‐ lyze how they can influence new platforms of communications and rein-‐ force new options for online press infographics.